2009
DOI: 10.1002/rcm.4191
|View full text |Cite
|
Sign up to set email alerts
|

Structure and end‐group analysis of complex hexanediol‐neopentylglycol‐adipic acid copolyesters by matrix‐assisted laser desorption/ionization collision‐induced dissociation tandem mass spectrometry

Abstract: Sequences and end groups of complex copolyesters were determined by fragmentation analysis by means of matrix-assisted laser desorption/ionization collision-induced dissociation tandem mass spectrometry (MALDI CID MS/MS). The complexity of the crude copolyester mixture was reduced by a chromatographic separation followed by a MALDI time-of-flight (TOF) investigation of fractions. Due to overlapping compositional and end-group information a clear assignment of end groups was very difficult. However, the fragmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 20 publications
0
21
0
1
Order By: Relevance
“…Both reactions could potentially be used to identify the MAA content in MAAcontaining copolymers. Other examples include the structural investigation of (R,S)-3-hydroxybutyrate/(R,S)-3-hydroxy-4-ethoxybutyrate copolyesters by ESI-MS/MS, as well as isocyanate oligomers 61,62 and poly(ester amide)s from sebacic acid and 4-amino-1-butanol by MALDI-CID-MS. 63 The mechanism of LACCC separation of copolyesters was confirmed by MALDI-MS/MS and the structure of different end-groups as well as short copolymer sequences was determined by Weidner et al 45 The ability of MALDI-and ESI-MS/MS for a structural assignment of individual end-groups of PMMA and PPO was shown by Jackson et al 64 The nature of the end-groups of novel azo-functional oligoesters synthesized through bulk ring opening of 3-caprolactone and D,L-lactide (LA) was shown in an ESI-MS/MS fragmentation experiment by Peptu et al 65 Polyesters and polyacrylates were investigated by Simonsick et al by means of laser desorption (LD) FT-ICR-MS. 66 The authors showed the advantages of using ultrahigh resolution FT-ICR-MS for the structural analysis and elucidation of the isomeric composition.…”
Section: Tandem Mass Spectrometrymentioning
confidence: 99%
“…Both reactions could potentially be used to identify the MAA content in MAAcontaining copolymers. Other examples include the structural investigation of (R,S)-3-hydroxybutyrate/(R,S)-3-hydroxy-4-ethoxybutyrate copolyesters by ESI-MS/MS, as well as isocyanate oligomers 61,62 and poly(ester amide)s from sebacic acid and 4-amino-1-butanol by MALDI-CID-MS. 63 The mechanism of LACCC separation of copolyesters was confirmed by MALDI-MS/MS and the structure of different end-groups as well as short copolymer sequences was determined by Weidner et al 45 The ability of MALDI-and ESI-MS/MS for a structural assignment of individual end-groups of PMMA and PPO was shown by Jackson et al 64 The nature of the end-groups of novel azo-functional oligoesters synthesized through bulk ring opening of 3-caprolactone and D,L-lactide (LA) was shown in an ESI-MS/MS fragmentation experiment by Peptu et al 65 Polyesters and polyacrylates were investigated by Simonsick et al by means of laser desorption (LD) FT-ICR-MS. 66 The authors showed the advantages of using ultrahigh resolution FT-ICR-MS for the structural analysis and elucidation of the isomeric composition.…”
Section: Tandem Mass Spectrometrymentioning
confidence: 99%
“…Daran schließt sich eine zweite Stufe der Massenanalyse zur Bestimmung der m / z ‐Werte der Fragment‐Ionen an. Solche Experimente zeigen einzelne Polymerendgruppen auf; dagegen gibt das eindimensionale MS‐Spektrum Aufschluss über die Summe der in dem Oligomer an den Kettenenden vorliegenden Substituenten, die auch eine oder mehrere unvollständige oder komplette Monomereinheiten enthalten können. Darüber hinaus kann die MS/MS eingesetzt werden, um Copolymersequenzen zu analysieren und Polymerstrukturen zu differenzieren, wie das in den Abschnitten 2.1 und 2.2 mit ausgewählten Beispielen veranschaulicht wird.…”
Section: Tandem‐massenspektrometrie (Ms/ms)unclassified
“…The addition of tandem MS (MS/MS) analysis in combination with both soft ionization techniques has made the structure analysis of homopolymers, as well as copolymers easier 13–20. However, only a few reports exist about the MS/MS analysis of copolymers using MALDI‐TOF21–23 and ESI 24–30. Wesdemiotis et al21 performed MALDI‐TOF MS/MS measurements on the poly(fluoro oxetane)‐ co ‐(tetrahydrofuran) copolymer to obtain information regarding its architecture.…”
Section: Introductionmentioning
confidence: 99%
“…The block copolymer mono‐ n ‐butyl ethers of poly(ethylene glycol)‐ b ‐poly(propylene oxide) (PEG‐ b ‐PPO) was analyzed by Weidner et al22 to determine the correct number of repeating units in the PEG and the PPO block of the copolymer. The end‐groups and segment information about complex copolyester samples was obtained by Weidner et al23 employing MALDI‐TOF MS/MS analysis. Adamus24 investigated two random biodegradable copolyester macromolecules by applying ESI ion trap MS combined with MS n .…”
Section: Introductionmentioning
confidence: 99%